The Effect of strategic Supremacy on strategic success A case study in Thi Qar Governorate - Hasan, Haneen Qasim; AL-SHEIKLI, ABDULRAZZAQ IBRAHEEM (Journal of Economics and Administrative Sciences, 2020)
Purpose To test the effect of strategic Supremacy on strategic success A case study in Thi Qar Governorate, methodology/approach – this is a mandatory entry. a case study was used and applied to the Department managers of Government of the province of Thi Qar, Research limitations/implications – It is clear that the strategic Supremacy variable is not being used effectively to achieve strategic success. Practical implications – use strategic supremacy positively to Support for strategic success. implementing and monitoring ignorance of them in how to use this supremacy to achieve strategic success and public serve So the researcher recommended giving Opportunities to those who have experience in the field of administration, law and other vital magazines that affect the work of the Governorate and provide them with those with experience who worked a long time in the Governorate, forming a solid team to discuss the methods that enhance the benefit of the Supremacy to achieve strategic success. Type of research: Research paper